The Relationship Between Psychological Distress of Nursing Faculty With Burnout - Mayantoinette F. Watson PhD, RN- (SAGE Publishing, 2023)
Introduction Approximately 83% of U.S. workers suffer from work-related stress. Burnout affects approximately 38% of nurses and nurse faculty per year. Contributing factors, including growing levels of mental health issues, can be seen among nursing faculty, leading to more and more nurses leaving nursing academia. Objectives This study objective aimed to identify associations between psychological distress with burnout in nursing faculty teaching in an undergraduate nursing program. Methods A quantitative design was utilized using a descriptive method with a convenience sample of nursing faculty ( n   =  150) from the Southeastern United States The Kessler Psychological Distress Scale was correlated with the Oldenburg Burnout Inventory. Regression analysis was used to analyze the data. Results Psychological distress was reported in 25% of the sample. Burnout was reported in 94% of the sample. Psychological distress and burnout were significantly correlated ( p  < .05). Race, gender, and age ( p  < .05) contributed to psychological distress. Conclusion Interventions promoting healthy mental well-being among nursing faculty are needed to address issues related to increasing rates of burnout and psychological distress. Implementation of workplace health promotion programs, increased mentorship, inclusion of diversity within nursing academia, and mental health awareness can improve mental health outcomes among nursing faculty. Further research is needed to explore the improvement of mental well-being among nursing faculty.